Norte de Santander Alumino silicates Minerals' Evaluation for the Big Scale Ceramic Pieces Manufacturing - Rozo-Rincón, Sandra Milena; Sánchez-Molina, Jorge; Gelves-Díaz, John Freddy (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This study shows the influence results of adding feldspar to clay materials from the metropolitan area of Cucuta (Colombia), in relation to key variables that are taken into account, when making a large format traditional ceramic product, through technical extrusion forming. The materials used were clays from the León and Guayabo formations, and the feldspar from the Sardinata town, all of which were studied by X-ray diffraction (XRD) and X-ray fluorescence (XRF). The specimens were formed in proportions of 100:0, 90:10 and 80:20 clay-feldspar, and were subjected to baking at temperatures of 950 °C-1000 °C-1050 °C. It was observed that the addition of feldspar, significantly improved the properties studied for all clays used in comparison with the standard mixture. The samples prepared with Támesis clay presented the best performance.